2015
DOI: 10.1155/2015/639494
|View full text |Cite
|
Sign up to set email alerts
|

Person-Centered Care in the Home Setting for Parkinson’s Disease: Operation House Call Quality of Care Pilot Study

Abstract: Objective. (1) To evaluate the feasibility of implementing and evaluating a home visit program for persons with Parkinson's disease (PD) in a rural setting. (2) To have movement disorders fellows coordinate and manage health care delivery. Background. The University of Florida, Center for Movement Disorders and Neurorestoration established Operation House Call to serve patients with PD who could not otherwise afford to travel to an expert center or to pay for medical care. PD is known to lead to significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Two studies reported the use of information technology–based platforms for the monitoring of patients’ day‐to‐day needs, coordination and feedback from the care provider, one utilized a telehealth solution . Other care coordination models used a ‘one‐stop‐clinic’ approach, where care providers from multiple domains met the patient at the same location over a day or two . Two models furthered this approach by taking health care provider teams to the patient's home .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported the use of information technology–based platforms for the monitoring of patients’ day‐to‐day needs, coordination and feedback from the care provider, one utilized a telehealth solution . Other care coordination models used a ‘one‐stop‐clinic’ approach, where care providers from multiple domains met the patient at the same location over a day or two . Two models furthered this approach by taking health care provider teams to the patient's home .…”
Section: Resultsmentioning
confidence: 99%
“…Other care coordination models used a ‘one‐stop‐clinic’ approach, where care providers from multiple domains met the patient at the same location over a day or two . Two models furthered this approach by taking health care provider teams to the patient's home . Yet another model of care coordination involved initial management at expert centers followed by routine care delivery at the community level through an integrated network of allied health care professionals .…”
Section: Resultsmentioning
confidence: 99%
“…Individuals who are older and have more chronic conditions are less likely to use the internet, 46,47 and the digital divide has hampered efforts to use technology to deliver PD care at home. 48 The divide can be overcome by delivering in-person home care to individuals with PD, 49 providing remote care via satellite clinics close to one’s home as is done in Canada, 22,37 engaging children in the care of their parents, and increasing access to telecommunication technologies. The digital divide is narrowing and the increasing ubiquity of smartphones, which are projected to be in the hands of 90% of individuals over age 6 by 2020, 50 provides a promising avenue to increase access to care, especially in resource limited countries like China and India.…”
Section: Overcoming Barriersmentioning
confidence: 99%
“…24 For some patients, care could be delivered in their own home. 25 In the 1930s, the house call was the primary means of providing care, and 40% of patientphysician encounters occurred there. 26 Dr. Jori Fleisher and colleagues have demonstrated the feasibility and value of providing such care from a Parkinson' specialist, nurse, and social worker.…”
Section: Clinic-centered Carementioning
confidence: 99%